John Dunn and the history of political theory. Issue 1 (2nd January 2021) - Cadeddu, Davide
ABSTRACT: In 1992, John Dunn published an essay in Italian (which came out in English only years later) in which he summarized and clarified certain aspects of his historiographical vision concerning the history of political theory. A careful analysis of the text – corroborated by a consideration of later comments as well as general historical-theoretical references – gives us an insight into the lights and shadows of his thought. This reinterpretation reveals the originality of a perspective that examined the meaning of 'canon' within the history of political theory, and indicated certain cultural and political aims to be consciously pursued through it. This original thought has recently been consolidated by other considerations on the need for a global history of political thought capable of offering interesting food for thought. Nevertheless, these seem to have emerged from a change of opinion on Dunn's part, focusing to a greater extent on certain (more or less well-defined) moral duties that should be pursued by scholars of the history of political thought.